COPYRIGHT AND RELATED RIGHTS INJUNCTIONS - Ana-Maria MARINESCU (Challenges of the Knowledge Society, 2021)
The national general copyright legislative framework, in particular, the national laws transposing the EU acquis related to online copyright infringement and enforcement procedures (IPRED, InfoSoc Directive, Conditional Access Directive, E-Commerce Directive, Rental Rights Directive, etc.), is providing, in case of copyright and related rights infringements, the possibility for the Courts to take measures against the infringers, especially injunctions. We can distinguish between interlocutory injunctions like provisional and precautionary measures and injunctions following a decision on case merits like blocking and take-down injunctions, including forward-looking, live and dynamic injunctions which are being increasingly applied to certain types of online rights infringements. The article will underline the national legal framework in the field and Romanian, European and international case-law.